Application of Problem Based Learning (PBL) Learning Model Assisted by Popular Article Media on Science Literacy of Students of Respiratory System Material Class VIII SMPN 7 Palangkaraya - Ihsanul ar mida; Nurul Septiana (JURNAL INOVASI PENDIDIKAN DAN SAINS, 2022)
: The researcher found that based on the interview results obtained according to the respiratory system material, it was relatively low, because in the respiratory system material obtained a value of 60.Therefore, it was applied through the Problem Based Learning (PBL) learning model assisted by popular article media on science literacy in the respiratory system material. There are several objectives in this study are: (1) knowing the influence of the Problem Basedd Learning (PBL) learning model assisted by popular article media on the science literacy of students of the respiratory system material class VIII SMPN 7 Palangkaraya, (2) knowing the influence of the Problem Based Learning (PBL) learning model assisted by popular article media on the learning outcomes of the class VIII respiratory system material at SMPN 7 Palangkaraya, (3) describing the application of the Problem Based Learning (PBL) learning model assisted by popular article media on the results of learning material for the respiratory system class VIII SMPN 7 Palangkaraya, (3) describing the application of the Problem Based Learning (PBL) learning model assisted by popular article media on science literacy of students of respiratory system material class VIII SMPN 7 Palangkaraya.This researcher used the Quasi method of research design experiment with Nonequivalent Control Group Design. This analysis was carried out by students of class VIII A and B at one of the schools of SMPN 7 Palangkaraya, the experimental class had 21 students and the control class had 21 students who used purposive sampling techniques. Data collection techniques are carried out using test and non-test methods. Data analysis techniques use normality tests, homogeneity tests and hypothesis tests. From the Learning Outcomes worth with the average N-gain of the Pretest experimental class is 66.67and Postest is 76.70, then the control class the pretest value is 44.09 and the postest is 56.73.Based on the hypothesis test results, namely Asmp.sig (2-tailed) worth 0.000<0.050 then Ha is accepted and Ho is rejected has significant changes. The application to the popular article media-assisted PBL learning model is very good, as this can be expressed by the average score of the first meeting obtained with a value of 3.33 and the second meeting obtained worth 3.34. . Based on the results of the research obtained, it can be categorized by the application of the PBL learning model assisted by popular article media, it is considered quite good for the science literacy of students of respiratory system material class VIII SMPN 7 Palangkaraya.